Copper-mediated arylation with arylboronic acids: Facile and modular synthesis of triarylmethanes - Rao, H. Surya Prakash; Rao, A. Veera Bhadra (Beilstein Journal of Organic Chemistry, 2016)
A facile and modular synthesis of triarylmethanes was achieved in good yield via a two-step sequence in which the final step is the copper(II)-catalyzed arylation of diarylmethanols with arylboronic acids. By using this protocol a variety of symmetrical and unsymmetrical triarylmethanes were synthesized. As an application of the newly developed methodology, we demonstrate a high-yielding synthesis of the triarylmethane intermediate towards an anti-breast-cancer drug candidate.
Keywords: copper; modular synthesis; triarylmethanes

(untitled) - Mondal, S.; Panda, G. (RSC Adv., 2014)

(untitled) - Nair, V.; Thomas, S.; Mathew, S. C.; Abhilash, K. G. (Tetrahedron, 2006)

(untitled) - Shchepinov, M. S.; Korshun, V. A. (Chem. Soc. Rev., 2003)

(untitled) - Duxbury, D. F. (Chem. Rev., 1993)

(untitled) - Oda, M.; Kawase, T.; Wei, C. (Pure Appl. Chem., 1996)

(untitled) - Mason, C. D.; Nord, F. F. (J. Org. Chem., 1951)

(untitled) - Ghaisas, V. V.; Kane, B. J.; Nord, F. F. (J. Org. Chem., 1958)

(untitled) - Irie, M. (J. Am. Chem. Soc., 1983)

(untitled) - Muthyala, R.; Katritzky, A. R.; Lan, X. (Dyes Pigm., 1994)

(untitled) - Rottman, C.; Grader, G.; De Hazan, Y.; Melchior, S.; Avnir, D. (J. Am. Chem. Soc., 1999)

(untitled) - Yamaguchi, K.; Tamura, Z.; Maeda, M. (Anal. Sci., 1997)

(untitled) - Heger, D.; Klánová, J.; Klán, P. (J. Phys. Chem. B, 2006)

(untitled) - Miura, T.; Urano, Y.; Tanaka, K.; Nagano, T.; Ohkubo, K.; Fukuzumi, S. (J. Am. Chem. Soc., 2003)

The Molecular Probes Handbook. A Guide to Fluorescent Probes and Labeling Technologies - Haugland, R. P. (Molecular Probes, 2005)

(untitled) - Urano, Y.; Kamiya, M.; Kanada, K.; Ueno, T.; Hirose, K.; Nagano, T. (J. Am. Chem. Soc., 2005)

(untitled) - Abe, H.; Wang, J.; Furukawa, K.; Oki, K.; Uda, M.; Tsuneda, S.; Ito, Y. (Bioconjugate Chem., 2008)

(untitled) - Kim, H. N.; Lee, M. H.; Kim, H. J.; Kim, J. S.; Yoon, J. (Chem. Soc. Rev., 2008)

(untitled) - Beija, M.; Afonso, C. A. M.; Martinho, J. M. G. (Chem. Soc. Rev., 2009)

(untitled) - Parai, M. K.; Panda, G.; Chaturvedi, V.; Manju, Y. K.; Sinha, S. (Bioorg. Med. Chem. Lett., 2008)

(untitled) - Shagufta; Srivastava, A. K.; Sharma, R.; Mishra, R.; Balapure, A. K.; Murthy, P. S. R.; Panda, G. (Bioorg. Med. Chem., 2006)

(untitled) - Bindal, R. D.; Golab, J. T.; Katzenellenbogen, J. A. (J. Am. Chem. Soc., 1990)

(untitled) - Jendralla, H.; Granzer, E.; von Kerekjarto, B.; Krause, R.; Schacht, U.; Baader, E.; Bartmann, W.; Beck, G.; Bergmann, A.; Kesseler, K.; Wess, G.; Chen, L.-J.; et al. (J. Med. Chem., 1991)

(untitled) - Costantino, L.; Ferrari, A. M.; Gamberini, M. C.; Rastelli, G. (Bioorg. Med. Chem., 2002)

(untitled) - Al-Qawasmeh, R. A.; Lee, Y.; Cao, M.-Y.; Gu, X.; Vassilakos, A.; Wright, J. A.; Young, A. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Mibu, N.; Yokomizo, K.; Uyeda, M.; Sumoto, K. (Chem. Pharm. Bull., 2003)

(untitled) - Schultz, T. W.; Sinks, G. D.; Cronin, M. T. D. (Environ. Toxicol., 2002)

(untitled) - Wang, P.; Kozlowski, J.; Cushman, M. (J. Org. Chem., 1992)

(untitled) - Long, Y.-Q.; Jiang, X.-H.; Dayam, R.; Sanchez, T.; Shoemaker, R.; Sei, S.; Neamati, N. (J. Med. Chem., 2004)

(untitled) - Cushman, M.; Kanamathareddy, S.; De Clerq, E.; Schols, D.; Goldman, M. E.; Bowen, J. A. (J. Med. Chem., 1991)

(untitled) - Parmar, V. S.; Bisht, K. S.; Jain, R.; Singh, S.; Sharma, S. K.; Gupta, S.; Malhotra, S.; Tyagi, O. D.; Vardhan, A.; Pati, H. N. (Indian J. Chem., Sect. B, 1996)

(untitled) - Bindal, R. D.; Katzenellenbogen, J. A. (J. Med. Chem., 1988)

(untitled) - Seligmann, O.; Wagner, H. (Tetrahedron, 1981)

(untitled) - Pindur, U.; Müller, J. (J. Heterocycl. Chem., 1987)

(untitled) - Witzel, H.; Pindur, U. (J. Heterocycl. Chem., 1988)

(untitled) - Sato, T.; Higuchi, S.; Ito, K. (Lett. Org. Chem., 2007)

(untitled) - Podder, S.; Choudhury, J.; Roy, U. K.; Roy, S. (J. Org. Chem., 2007)

(untitled) - Kodomari, M.; Nagamatsu, M.; Akaike, M.; Aoyama, T. (Tetrahedron Lett., 2008)

(untitled) - Yamamoto, Y.; Itonaga, K. (Chem. – Eur. J., 2008)

(untitled) - Genovese, S.; Epifano, F.; Pelucchini, C.; Curini, M. (Eur. J. Org. Chem., 2009)

(untitled) - Hikawa, H.; Suzuki, H.; Azumaya, I. (J. Org. Chem., 2013)

(untitled) - Li, Z.; Duan, Z.; Kang, J.; Wang, H.; Yu, L.; Wu, Y. (Tetrahedron, 2008)

(untitled) - Shirakawa, S.; Kobayashi, S. (Org. Lett., 2007)

(untitled) - Thirupathi, P.; Kim, S. S. (Tetrahedron, 2010)

(untitled) - Shacklady-McAtee, D. M.; Roberts, K. M.; Basch, C. H.; Song, Y.-G.; Watson, M. P. (Tetrahedron, 2014)

(untitled) - Harris, M. R.; Hanna, L. E.; Greene, M. A.; Moore, C. E.; Jarvo, E. R. (J. Am. Chem. Soc., 2013)

(untitled) - Zhou, Q.; Srinivas, H. D.; Dasgupta, S.; Watson, M. P. (J. Am. Chem. Soc., 2013)

(untitled) - Tabuchi, S.; Hirano, K.; Satoh, T.; Miura, M. (J. Org. Chem., 2014)

(untitled) - Matthew, S. C.; Glasspoole, B. W.; Eisenberger, P.; Crudden, C. M. (J. Am. Chem. Soc., 2014)

(untitled) - Nambo, M.; Crudden, C. M. (Angew. Chem., Int. Ed., 2014)

(untitled) - Nambo, M.; Crudden, C. M. (ACS Catal., 2015)

(untitled) - Rao, H. S. P.; Rao, A. V. B. (Eur. J. Org. Chem., 2014)

(untitled) - Rao, H. S. P.; Rao, A. V. B. (J. Org. Chem., 2015)

(untitled) - Boymond, L.; Rottländer, M.; Cahiez, G.; Knochel, P. (Angew. Chem., Int. Ed., 1998)

(untitled) - Majumdar, K. K.; Cheng, C.-H. (Org. Lett., 2000)

(untitled) - Niwa, T.; Yorimitsu, H.; Oshima, K. (Org. Lett., 2007)

(untitled) - Yu, J.-Y.; Kuwano, R. (Org. Lett., 2008)

(untitled) - Cao, X.; Sha, S.-C.; Li, M.; Kim, B.-S.; Morgan, C.; Huang, R.; Yang, X.; Walsh, P. J. (Chem. Sci., 2016)

(untitled) - Chan, D. M. T.; Monaco, K. L.; Wang, R.-P.; Winters, M. P. (Tetrahedron Lett., 1998)

(untitled) - Lam, P. Y. S.; Clark, C. G.; Saubern, S.; Adams, J.; Winters, M. P.; Chan, D. M. T.; Combs, A. (Tetrahedron Lett., 1998)

(untitled) - Evans, D. A.; Katz, J. L.; West, T. R. (Tetrahedron Lett., 1998)

(untitled) - Itoh, T.; Shimizu, Y.; Kanai, M. (Org. Lett., 2014)

VOGEL’s Textbook of Practical Organic Chemistry - Furniss, B. S.; Hannaford, A. J.; Smith, P. W. G.; Tatchell, A. R. (John Wiley & Sons, 2077)

(untitled) - Kodomari, M.; Satoh, H.; Yoshitomi, S. (J. Org. Chem., 1988)

(untitled) - Lu, J.; Guan, Z.-Z.; Gao, J.-W.; Zhang, Z.-H. (Appl. Organomet. Chem., 2011)